Synthesis and Characterization of Macrocyclictetradentate Ligand Type N2o2 and its Complexes with (Co(Ii), Ni(Ii) And Pd(Ii)) - Hasan, Hasan Ahmad (Al-Nahrain Journal of Science, 2018)
The Schiff base ligand [2,3,8,9–tetra -methyl-1,4,5,7,10,12-hexa azo-5,12- dihydro -6,11- dione 1,3,7,10-dudec-tetra-ene] [H2L] and its complexes with ( Co(II), Ni(II) and Pd(II)) was prepared in two steps. In the first a solution of (2,5-Hexandion) in methanol react under reflux with (semicarbazidhydrochlorid) in 1:2 mole ratio to give an intermediate compound [2,5-Hexandion bis (Semicarbazone)] which react in the second step with another mole of ( 2,5-Hexandion) giving the mentioned ligand. The complexes were then synthesized by direct reaction of the corresponding metal chloride with the ligand. The ligand and complexes have been characterized by spectroscopic methods [IR, (UV-Vis), HPLC and (A.A)], chloride content and conductivity measuremenst. The data of these measurements suggest a square planar geometry around Ni(II) and Pd(II) ions and a tetrahedral geometry around Co(II) ion.